Improved redox homeostasis owing to the up-regulation of one-carbon metabolism and related pathways is crucial for yeast heterosis at high temperature - Song, Liang; Shi, Jun-Yan; Duan, Shou-Fu; Han, Da-Yong; Li, Kuan; Zhang, Ri-Peng; He, Peng-Yu; Han, Pei-Jie; Wang, Qi-Ming; Bai, Feng-Yan (Genome Research, 2021)
Heterosis or hybrid vigor is a common phenomenon in plants and animals; however, the molecular mechanisms underlying heterosis remain elusive, despite extensive studies on the phenomenon for more than a century. Here we constructed a large collection of F1 hybrids of Saccharomyces cerevisiae by spore-to-spore mating between homozygous wild strains of the species with different genetic distances and compared growth performance of the F1 hybrids with their parents. We found that heterosis was prevalent in the F1 hybrids at 40°C. A hump-shaped relationship between heterosis and parental genetic distance was observed. We then analyzed transcriptomes of selected heterotic and depressed F1 hybrids and their parents growing at 40°C and found that genes associated with one-carbon metabolism and related pathways were generally up-regulated in the heterotic F1 hybrids, leading to improved cellular redox homeostasis at high temperature. Consistently, genes related with DNA repair, stress responses, and ion homeostasis were generally down-regulated in the heterotic F1 hybrids. Furthermore, genes associated with protein quality control systems were also generally down-regulated in the heterotic F1 hybrids, suggesting a lower level of protein turnover and thus higher energy use efficiency in these strains. In contrast, the depressed F1 hybrids, which were limited in number and mostly shared a common aneuploid parental strain, showed a largely opposite gene expression pattern to the heterotic F1 hybrids. We provide new insights into molecular mechanisms underlying heterosis and thermotolerance of yeast and new clues for a better understanding of the molecular basis of heterosis in plants and animals.